The Effectiveness of the Social Commerce and E-Commerce Separation System in the Implementation of Minister of Trade Regulation Number 31 of 2023 - NURUL APRIYANI; Titi Stiawati; Arenawati Arenawati (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
The transformation of Indonesia's digital trade ecosystem after the COVID-19 pandemic has given rise to social commerce a model that combines social media functions with online transactions creating an urgent need for more adaptive regulation. This study examines the effectiveness of the separation system between social commerce and e-commerce as regulated by the Minister of Trade Regulation (Permendag) No. 31 of 2023, which aims to restructure digital trade governance and protect micro, small, and medium enterprises (MSMEs). The research aims to assess how effectively the policy achieves market fairness, strengthens platform supervision, and fosters a competitive digital ecosystem. This study employs a qualitative descriptive approach through literature review and observation of implementation practices on platforms such as TikTok, Instagram, and Tokopedia. The analysis applies the Adaptive Policy Design & Governance Capacity framework (Capano & Woo, 2018), covering analytical, operational, and political capacities, as well as policy robustness, adaptiveness, and integration. The results indicate that Minister of Trade Regulation No. 31/2023 is normatively effective in clarifying the boundary between promotional and transactional functions, while encouraging global corporate compliance through the TikTok Shop Tokopedia merger. The policy is found to be robust, adaptive, and well-coordinated across institutions, although challenges remain in oversight and MSME digital literacy. This study highlights the importance of adaptive and collaborative governance capacity in balancing innovation with regulation and provides a foundation for strengthening inclusive and sustainable digital trade governance in Indonesia.